Effect of Sustainable HRM Practice on Organizational Performance Mediated by Knowledge Management, Work Engagement and Organizational Culture - Yuswardi, Yuswardi; Asri, Dhita Hafizha; Saputra, Osgood Feriady Darma (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The manufacturing sector is currently under significant pressure to enhance productivity and sustainability due to rapid industry changes, technological advancements, and intensified global competition. This creates an urgent need for integrating sustainable Human Resource Management (HRM) practices to support long-term organizational performance. This study investigates the impact of sustainable HRM practices on organizational performance within the manufacturing industry in Batam, Indonesia. Employing a quantitative research approach, data were collected through structured questionnaires distributed to 370 employees across multiple companies. The research involved several stages of data analysis, including validity testing, reliability analysis, and structural equation modelling (SEM), to evaluate the hypothesized relationships among variables. The results revealed that sustainable HRM practices significantly influence knowledge management, work engagement, and organizational culture, which collectively enhance organizational performance. These findings imply that manufacturing firms should emphasize the development of sustainable HRM strategies, such as effective knowledge sharing systems and fostering a positive organizational environment. Implementing such practices will improve employee engagement, promote innovation, and sustain competitive advantage. Overall, this research underscores the importance of integrating sustainability initiatives into HRM practices to achieve resilient and high-performing manufacturing organizations.